Development of the Pediatric Social Risk Instrument Using a Structured Panel Approach. (October 2018) - Cohen-Silver, Justine; Adams, Sherri; Agrawal, Rishi; Birken, Catherine; Cohen, Eyal; Dougherty, Geoffrey; Houtrow, Amy; Jegathesan, Thivia; Kandasamy, Sharmilaa; Muskat, Barbara; Pai, Nikhil; Maguire, Jonathon L.
Background . Social determinants of health impact child illness. Currently, no instrument exists to identify social need during hospital admission. Methods . Using the UCLA (University of California Los Angeles)-RAND appropriateness method, consensus was reached for an instrument to identify social need in hospitalized children. A panel of 11 experts reviewed candidate indicators through 3 rounds to reach consensus. The instrument then underwent usability testing. Results . Three hundred and forty-seven indicators from the literature were sorted into 18 social risk themes. After 3 rounds, consensus was reached on 82 indicators. Six additional social risk themes were recommended by the panel, resulting in consensus for 18 additional indicators. Final refinement resulted in an instrument containing 86 indicators representing 11 social risk themes. Usability testing identified that the tool was well received by families. Final feedback was incorporated into a post-usability instrument. Conclusions . Using the UCLA-RAND appropriateness method, a new pediatric social risk instrument was created to identify social need for hospitalized children.